SYNTHESIS AND MOLECULAR DOCKING STUDY OF CAFFEINE DERIVATIVES TOWARDS ENZYMES INVOLVED IN ALZHEIMERâS DISEASE - Ayu Rachmadhaningtiyas, Dyah
Caffeine (1) is the most extensively studied purine alkaloid. Purine consists of pyrimidine and imidazole rings, making it the most widely distributed nitrogenous heterocycle in nature. Drugs containing purines exhibit diverse biological activities such as antiviral, anti-inflammatory, bronchodilator, immunosuppressive, cytokinin, and antimicrobial activities. Caffeine (1) is widely regarded as a central nervous system (CNS) stimulant that plays a crucial role in stimulating the cerebral cortex. Additionally, caffeine (1) also shows significant effects on cellular function and regulation, apoptosis, and DNA repair. Caffeine (1) is the most widely consumed psychoactive substance in the world. Regular consumption of caffeine (1) from both coffee and tea provides neuroprotective effects that may slow the progression of Alzheimer's disease. Alzheimer's is caused by damage to brain cells or is a neurodegenerative disorder that develops progressively, with an average duration of 8.5 years from the onset of clinical symptoms to death. In 2020, 50 million people worldwide were diagnosed with this disease, with 10 million new cases annualy. There are three pathogenesis mechanisms of Alzheimer's disease, one of which is the cholinergic hypothesis. This hypothesis is characterized by a decrease in acetylcholine levels in the brain. Treatment of this disease can be performed using small-molecule acetylcholinesterase enzyme inhibitors. In the use of caffeine derivatives (1) to treat Alzheimer's disease, the potential of caffeine (1) as an acetylcholinesterase inhibitor was increased through chemical transformation at C-8. Based on this background, the objective of this research was to determine the inhibitory potential of various 8-substituted caffeine derivatives against acetylcholinesterase using in silico methods, including molecular docking and molecular dynamics simulations. The second objective was to synthesize 8-substituted caffeine derivatives via the intermediate compound 8-fluorocaffeine (2). The third objective was to study the activity of the synthesized compounds as acetylcholinesterase inhibitors in vitro. Molecular docking was performed to determine the potential of 8-substituted caffeine derivatives as acetylcholinesterase inhibitors using YASARA v21.6.17 application. Compounds that can interact hydrophobically with acetylcholinesterase enzymes have the potential to be acetylcholinesterase inhibitors. Therefore, 41 caffeine compounds substituted with various hydrophobic groups were selected. These caffeine derivatives consisted of 19 8-substituted aminocaffeine compounds (3 21) and twenty-three 8-substituted alkoxycaffeine compounds (22 44). The similarity prediction of the 8-substituted caffeine derivatives to drug-like compounds was performed using the in silico web tool SwissADME, based on Lipinski's rule. Some of the most promising compounds were then subjected to molecular dynamics simulations using YASARA v21.6.17 application. Next, the transformation of caffeine (1) through the intermediate compound 8-fluorocaffeine (2), obtained from the fluorination reaction of caffeine (1) using Selectfluor®, which is a new method, was carried out. The transformation of 8-fluorocaffeine (2) was performed using nucleophiles with various amine or alcohol groups. The structures of the synthesized compounds were determined based on NMR spectroscopy, mass spectrometry, infrared spectroscopy, and UV-vis spectroscopy. Compounds with chiral centers were further analyzed using Circular Dichroism (CD) and ECD.The activity of the synthesized compounds as acetylcholinesterase inhibitors was tested in vitro using a modified Ellman colorimetric method. Based on the molecular docking results of 41 8-substituted caffeine derivatives, all of these compounds exhibited better binding affinity values than caffeine (1), specifically is lower than -6.8 kcal/mol. Among them, 14 compounds, including seven 8-substituted aminocaffeine derivatives (14, 16 21) and seven 8-substituted alkoxycaffeine derivatives (36 40, 43, 44), even had binding affinity values lower than -10 kcal/mol. These values were comparable to the binding affinity values obtained for commercial drug compounds (galantamine and donepezil), which were also tested for molecular docking in this study. The similarity between these 14 compounds and drug-like compounds was predicted using SwissADME. Based on these results, 13 compounds met the similarity criteria, but one compound, 8,8'-((4-acetyl-1,3-phenylene)bis(oxy))bis(caffeine) (39), did not meet the similarity criteria. Next, molecular dynamics simulations were conducted on six compounds with the lowest binding affinity values and the highest binding similarity values compared to galantamine and donepezil. Based on the molecular dynamics simulation results, compound 8-((3-aminophenyl)amino)caffeine (20) exhibited the most stable RMSD profile over 100 ns, with an average RMSD value of 0.761 Å and an RMSD range of 1.255 Å, indicating that this molecule has the most potential as an acetylcholinesterase inhibitor. Futhermore, the synthesis of fourteen compounds with the highest potential were synthesized based on molecular docking. These compounds were substituted by aromatic groups. To evaluate the structure-activity relationship of acetylcholinesterase inhibitors more broadly and deeply, 10 additional compounds substituted with aliphatic groups were also synthesized. Therefore, 24 8-substituted derivatives were synthesized, including 14 aminocaffeine derivatives and 10 alkoxycaffeine derivatives. Among them, ten compounds were newly synthesized, consisting of three aminocaffeine derivatives (8-(azetidin-1-yl)caffeine (10), 8-(3-chloro-4-fluorophenyl)aminocaffeine (19), and 8-((3-aminophenyl)amino) caffeine (20)), and seven alkoxycaffeine derivatives 8-((tetrahydrofuran-3- yl)oxy)caffeine (31), 8-(4-((2-isopropoxyethoxy)methyl)- phenoxy)caffeine (35), 8-(4-(3-oxobutyl)phenoxy)caffeine (37), 8-(4-acetyl-3-hydroxyphenoxy)caffeine (38), 8,8'-((4-acetyl-1,3-phenylene)bis(oxy))bis(caffeine) (39), 8-(4-allyl-2 methoxyphenoxy)caffeine (43), and 8-(2-methoxy-4-(prop-1-en-1 yl)phenoxy)caffeine (44). The 8-substituted aminocaffeine derivatives were synthesized by reacting 8-fluorocaffeine (1) with various amines in ethanol under reflux conditions. Meanwhile, only the synthesis of 8-(azetidin-1-yl)caffeine (10) was carried out in acetonitrile solvent under reflux conditions with the addition of cesium carbonate. The synthesis of 8-substituted aminocaffeine derivatives yielded products with yields ranging from 15.3% to 99.5%. Furthermore, 8-substituted alkoxycaffeine derivatives were synthesized by reacting 8-fluorocaffeine (1) with various alcohols in acetonitrile under reflux conditions with the addition of excess KOH, resulting in products with yields of 10.9% 99.4%. In vitro tests as acetylcholinesterase inhibitors were conducted on the 24 synthesized compounds, as well as caffeine (1) and 8-fluorocaffeine (2), at a concentration of 10 ?M, using positive controls, galantamine (49) and sunitinib (124). Based on the test results, caffeine (1) and 8-fluorocaffeine (2) showed no inhibitory activity, whereas the other 24 compounds exhibited inhibitory activities ranging from 0 to 60%. Four cyclic amine-substituted caffeine derivatives (10 12) demonstrated better inhibitory activity (20 amine-substituted caffeine derivatives (14 21) (0 60%) than eight aromatic 26%). Meanwhile, two other caffeine compounds substituted with aliphatic amine (4) or short-chain aliphatic alcohol (22) did not inhibit acetylcholinesterase enzyme (0%). Another caffeine compound substituted with a long-chain aliphatic amine (9), showed relatively good inhibitory activity (45%). Additionally, caffeine substituted with a cyclic alcohol (31) and caffeine substituted with various types of phenolic groups (35–40, 43, 44) showed an increase in inhibitory activity compared to caffeine (1), although the activity remained relatively weak (8–43%). Among all the compounds tested, 8-(azetidin-1-yl)caffeine (10) had the highest inhibition percentage, at 60.6 ± 3.1%, with an IC50 value of 5.19 ± 0.48 ?M. Importantly, compound 10 was not the most promising based on molecular docking results (binding affinity value of -8.3 kcal/mol), so compound 10 was not tested for drug-similarity or molecular dynamics simulation. Consequently, compound 10 was further tested in silico to determine its similarity based on Lipinski's rule, molecular dynamics simulation. The results of in silico testing showed that compound 10 met all five Lipinski's rules, indicating similarity to commercial drug compounds. Molecular dynamics simulation results showed that compound 10 had an average RMSD of 1.204 Å and a range of 0.699 Å. This indicates that compound 10 has a similar stability to Alzheimer's drug compounds, namely galantamine (49) and donepezil (48) . Based on these results, 41 8-substituted caffeine derivatives showed better binding affinity in silico than caffeine (1). This indicated the potential of these compounds as acetylcholinesterase inhibitors. Subsequently, the synthesis of 24 8-substituted caffeine derivatives using intermediate 8-fluorocaffeine (2) was successfully performed, and several compounds were produced in excellent yields. In vitro tests showed that of the 24 synthesized compounds, 19 caffeine derivatives had higher acetylcholinesterase inhibitory activity values than caffeine. Notably, compound 8-(azetidin-1-yl)caffeine (10) exhibited the highest inhibition percentage of 60.6 ± 3.1% and an IC50 value of 5.19 ± 0.48 ?M. Further in silico testing of compound 10 confirmed that compound 10 not only met the criteria as an Alzheimer's drug candidate based on Lipinski's rule, but also showed stability comparable to that of commercial drugs such as galantamine (49) and donepezil (48) in molecular dynamics simulations. The results also indicate that caffeine derivatives with cyclic amine substituents could serve as a basis for the development of effective drugs for Alzheimer's disease. (formula)